Towards detection of endotoxin in high-purity water utilising a surface plasmon resonance biosensor - Barrett, G. (Cranfield University, 2000)
The aims of this project were to develop a system for monitoring a continuous stream of high grade purified water for potential contamination by bacterial endotoxins. The monitoring system was to be designed so that it could be readily integrated within a closed water purification processing system. The project was viewed as a developmental stage towards the development of a commercial sensor with wide ranging applications within the pharmaceutical and environmental sectors. This text details the development of testing protocols for the examination of ultra pure water using different sensing matrices. The endotoxin structure is comprised of three main sections with specific chemistry. These regions have each been considered as potential areas for detection. The development of surface plasmon resonance (SPR) systems and protocols for the detection of endotoxin was shown both to be possible and practical within given experimental parameters. In order to assess the potential for this sensing within a more established experimental system and to further expand the potential sensing layers for endotoxins, further experiments were carried out using a BIAcore system. The use of the BIAcore allowed the examination of alternative sensing surfaces based on the specific nature of the endotoxin molecule rather than the use of literature based reactants that have previously displayed an affinity for the endotoxin molecules. The methods used within this project have concentrated on the overall chemistry of the endotoxin molecule. The potential binding/complexing agents have been targeted at the three principal regions of the endotoxin structure using the chemical nature of these regions as an attractive surface to the sensing layer.